2015
DOI: 10.1016/j.encep.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives actuelles dans la microdélétion 22q11.2 : prise en charge du phénotype neurocomportemental

Abstract: Required pharmacological treatment strategies have to be adapted to the syndrome. Moreover, cognitive remediation is a promising tool for treating neuro- and social cognitive deficits in 22q11.2DS. However, these new therapeutic strategies have to be developed to improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Swillen et al, 1997;Campbell, McCabe, Melville, Strutt, & Schall, 2015). Underlying social-cognitive deficits are assumed to be a precipitating factor for these limitations and socio-cognitive remediation is suggested for enhancing sociocommunicative skills and overall quality of life (Demily et al, 2015;Swillen & McDonald-McGinn, 2015). However, (longitudinal) research is needed to delineate the most effective management for individuals with 22q11.2DS in different stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…Swillen et al, 1997;Campbell, McCabe, Melville, Strutt, & Schall, 2015). Underlying social-cognitive deficits are assumed to be a precipitating factor for these limitations and socio-cognitive remediation is suggested for enhancing sociocommunicative skills and overall quality of life (Demily et al, 2015;Swillen & McDonald-McGinn, 2015). However, (longitudinal) research is needed to delineate the most effective management for individuals with 22q11.2DS in different stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with fragile X syndrome, the same measure has been found to be related to excessive displays of anxiety, which involve stereotypical movement and repetitive self-injurious behaviour (Woodcock et al 2009a(Woodcock et al , 2009bWoodcock et al 2010;Woodcock et al 2011). Demily et al (2014) found that the 22q11.2 deletion syndrome, which is characterised by difficulties in sustaining attention, executive function, memory and visualspatial perception, not only presents a high rate of bipolar disorder and major depression, especially in adolescence and young adulthood, but also anxiety disorders and schizophrenia in adulthood (Gothelf et al 2008;Santambrogio et al 2020). Zarchi et al (2014 compared the neuropsychiatric and neurocognitive phenotypes of this syndrome with those of Williams syndrome, which also has a lower Performance-IQ than Verbal-IQ but shows more severe impairment of visuospatial functions.…”
Section: Introductionmentioning
confidence: 99%
“…Demily et al . (2014) found that the 22q11.2 deletion syndrome, which is characterised by difficulties in sustaining attention, executive function, memory and visualspatial perception, not only presents a high rate of bipolar disorder and major depression, especially in adolescence and young adulthood, but also anxiety disorders and schizophrenia in adulthood (Gothelf et al . 2008; Santambrogio et al .…”
Section: Introductionmentioning
confidence: 99%
“… 3–6 The majority of cases result from heterozygous chromosomal deletion in the above-mentioned region. The size of the deleted chromosomal region has been reported in different series to be around 0.7–3 million base pairs 7 As a result of this deletion, several genes are lost, including HIRA protein (HIRA), T-box 1 protein (TBX1), Catechol-O-methyltransferase (COMT), and Recombinant Human Crkl (CRKL). 8–10 These genes are related to the formation and development of the pharyngeal arches (PA) and the migration of neural crest cells; for that reason, the genetic disruption of these genes alters various structures, resulting in conditions such as conotruncal cardiac anomalies, thymus hypoplasia, hypocalcemia resulting from lack of development of the parathyroid glands, cognitive deficits, frequent infections, and autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%